Employer association in Italy: Trends and economic outcomes - Bernardo Fanfani; Claudio Lucifora; Daria Vigani (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
This paper analyses the characteristics of employer association in Italy, using unique firm-level data with information on employers' affiliation choices as well as their characteristics. We document that a persistent decline in affiliation rates to employers' associations has occurred during the last two decades. We show that affiliated companies are positively selected, as they tend to be larger, older, more likely to be located in richer regions, to be export- and innovation-oriented, as well as more likely to provide training. Using longitudinal data and regression decomposition techniques, we show that more fragile and less innovative firms have been more affected by the persistent decline in affiliation rates. Using a firm fixed effect identification strategy, we also show that firms that become members of an employer association tend to experience a faster growth in employment, but there are no significant relationships with productivity dynamics. Finally, the paper analyses whether the level of representativeness of employers' associations has any effect on bargaining outcomes concerning the level of minimum wages, which are settled by these organizations in national industry-wide collective contracts after a negotiation process with trade unions. Results from this analysis show that a higher representativeness of employers' organizations has a weak positive relationship with the level of bargained wages.
Keywords: 52; J31; J41; 330; industrial relations; employer association; collective bargaining; wage setting